Exploring the nutritional and phytochemical potential of sorghum in food processing for food security. Issue 2 (24th October 2018) - Chhikara, Navnidhi; Abdulahi, Burale; Munezero, Claudia; Kaur, Ravinder; Singh, Gurpreet; Panghal, Anil
Abstract : Purpose: Sorghum is quite comparable to wheat, rich source of nutrients with various health benefits, and therefore considered as a grain of future. The purpose of this paper is to review the bioactive active compounds, health benefits and processing of the sorghum. Sorghum is utilized for animal feeding rather than the human food usage. Therefore, this paper focuses on the emerging new health foods with benefits of the sorghum. Design/methodology/approach: Major well-known bibliometric information sources searched were the Web of Science, Google Scholar, Scopus and PubMed. Several keywords like nutritional value of sorghum, bioactive compounds present in sorghum, health benefits of sorghum and processing of sorghum were chosen to obtain a large range of papers to be analyzed. A final inventory of 91 scientific sources was made after sorting and classifying them according to different criteria based on topic, academic field country of origin and year of publication. Findings: From the literature reviewed, sorghum processing through various methods, including milling, malting, fermentation and blanching, bioactive compounds, as well as health benefits of sorghum were found and discussed. Originality/value: Through this paper, possible processing methods and health benefits of sorghum are discussed after detailed studies of literature from journal articles.